Quantitative Literacy-based Laboratory Activity Design on the Effect of Color Spectra on Photosynthetic Rate - Yuniarti, Anisyah; Ningsih, Kurnia; Supriatno, Bambang; Faturrahman, Mas Akhbar; Haruno, Mai (Biosaintifika: Journal of Biology & Biology Education, 2025)
The Ingenhousz photosynthesis experiment conducted in schools aims to verify the concept of plants producing oxygen. However, opportunities to develop students’ quantitative literacy and train science process skills (SPSs) remain limited, as photosynthesis experiments commonly employed in schools are predominantly qualitative. This research aimed to develop an alternative photosynthesis laboratory activity design (LAD) based on an analysis of existing LADs to enhance students’ quantitative literacy and SPSs. Using the Research and Development (R&D) method, this research focused on the effect of color spectra on photosynthetic rate—an aspect that presents novelty of this research. The existing LADs were analyzed in terms of relevance, competence, knowledge construction, and practical aspects, resulting in 83.3% (very good), 43.1% (fair), 58.3% (fair), and 55.6% (fair), respectively. The analysis results of these four aspects are the basis for developing the alternative LAD. The alternative LAD was developed and then validated, resulting in a validity value of 0.915, which is categorized as valid. The alternative LAD trial demonstrated that it can collect quantitative data and enhance students’ quantitative literacy and SPSs, with the blue light spectrum producing the highest photosynthetic rate at 0.4 ml/g. The quantitative literacy-based LAD fosters data-driven thinking crucial for future scientific inquiry. This supports cultivating more analytically skilled students equipped to face real-world environmental and scientific challenges.